Pengaruh Instar Larva Inang Spodoptera litura Fabricius (Lepidoptera: Noctuidae) terhadap Keberhasilan Hidup Parasitoid Eriborus argenteopilosus Cameron (Hymenoptera: Ichneumonidae) - Novri Nelly; Yunisman Yunisman; Yulia Rahmawati (Perhimpunan Entomologi Indonesia, 2011)
Research on the effect of host larval stage on survivorship of the parasitoid E. argenteopilosus was conducted under laboratory conditions. Survivorship was studied by using S. litura larval with different stage (1st, 2nd, 3rd, and 4th instars). Result of the research indicated that development rate of the parasitoid E. argenteopilosus is faster when reared on 3rd instar larvae. The higher the level of host-instar larvae, shorter time was needed to complete the parasitoid’s life cycle. Only 4.67% of the larvae completed its development to pupal stage, and only 1% reached adulthood, with males being the dominant of the emerging adults.